ENGLISH BREVET TERMS IN INDONESIAN MILITARY: A STUDY OF ACRONYM AND INITIALISM - Wedhowerti, Wedhowerti; Prasetya, Hermawan Adi (University of Muhammadiyah Malang, 2024)
This research aims at providing detailed explanation on how English brevet terms in Indonesian military are formed and reasons why those are classified as acronym and initialism. English brevet terms used in Indonesian military are difficult to understand due to their polysemic nature. The knowledge of internal structure of each term is important in order to ease the process of understanding the terms. Employing morphological approach and qualitative in nature, the research yields twenty English brevet terms in Indonesian military. The data are collected from websites of Indonesian military and selected based on their use in military domain. Those are classified and analyzed based on English phonotactic rules. This study reveals that ten are acronyms and ten are classified as initialisms and they mostly have the combination of Noun+Noun formation. This study highlights the importance of doing morphological research on military terms as many military terms to denote new concepts in military domain are not examined yet.